(untitled) (Scientific journal of the Fergana State University, 2024)
Purpose of the study: The article describes the emergence of human needs and interests in the information society, its important aspects, factors, purpose and essence. Research methods: Dialectics, analysis and synthesis, historicity, observation. Research results: During the study of the topic, the definitions of the concepts of needs and interests in the research of scientists and in dictionaries were compared. As a conclusion, a socio-philosophical analysis of conflicts in meeting the needs and interests of young people in the information space is given.